2019
DOI: 10.1021/acs.jproteome.8b00982
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Analysis of Lewy Body-Enriched α-Synuclein in Parkinson’s Disease

Abstract: Parkinson's disease (PD) is characterized by intraneuronal inclusions of aggregated α-synuclein protein (so-called Lewy bodies) in distinct brain regions. Multiple posttranslational modifications may affect the structure and function of α-synuclein. Mass spectrometry-based analysis may be useful for the characterization and quantitation of α-synuclein forms, but has proven challenging, mainly due to the insolubility of Lewy bodies in aqueous buffer. In the present study, we developed a novel method by combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 59 publications
3
64
0
Order By: Relevance
“…Deletion of only the last 10 amino acids is already sufficient to accelerate ␣-Syn aggregation in vitro, and this effect is stronger upon larger C-terminal truncations up to amino acids 102-120 [24][25][26]. ␣-Syn is subject to several post-translational modifications (PTMs), including N-terminal acetylation, ubiquitylation, SUMOylation, nitration, and phosphorylation [27][28][29][30][31][32], with diverse consequences for its function and propensity to aggregate (detailed below). Several roles have been ascribed to ␣-Syn, including facilitating the assembly of N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE)-complexes at presynaptic neuron terminals that mediate release of neurotransmitters [33,34], and induction of membrane curvatures [35], among many others [36].…”
Section: Alpha-synuclein Structure and Functionmentioning
confidence: 99%
“…Deletion of only the last 10 amino acids is already sufficient to accelerate ␣-Syn aggregation in vitro, and this effect is stronger upon larger C-terminal truncations up to amino acids 102-120 [24][25][26]. ␣-Syn is subject to several post-translational modifications (PTMs), including N-terminal acetylation, ubiquitylation, SUMOylation, nitration, and phosphorylation [27][28][29][30][31][32], with diverse consequences for its function and propensity to aggregate (detailed below). Several roles have been ascribed to ␣-Syn, including facilitating the assembly of N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE)-complexes at presynaptic neuron terminals that mediate release of neurotransmitters [33,34], and induction of membrane curvatures [35], among many others [36].…”
Section: Alpha-synuclein Structure and Functionmentioning
confidence: 99%
“…Acetylation is also an outstanding α-synuclein PTM as it is found in Lewy bodies and brain regions affected in the disease ( Anderson et al, 2006 ; Ohrfelt et al, 2011 ; Kellie et al, 2014 ; Bhattacharjee et al, 2019 ). Obliteration of α-synuclein acetylation sites in vivo leads to its enhanced aggregation and toxicity in primary neurons and mice ( de Oliveira et al, 2017 ), implying that acetylation may prevent α-synuclein aggregation.…”
Section: Overview Of α-Synuclein Post-translational Modificationsmentioning
confidence: 99%
“…Later, it was identified by mass spectrometry analysis in both purified Lewy bodies ( Anderson et al, 2006 ; Bhattacharjee et al, 2019 ) and lysates of PD tissues ( Ohrfelt et al, 2011 ; Kellie et al, 2014 ), and shown to occur at different α-synuclein residues at the C- and N-termini (for more details see Table 1 ). Although not all reported α-synuclein truncations were found enriched in Lewy bodies or PD tissues ( Ohrfelt et al, 2011 ; Kellie et al, 2014 ; Bhattacharjee et al, 2019 ), the importance of truncations is implied by their increased tendency to aggregate in vitro , in cell lines and in vivo models ( Crowther et al, 1998 ; Liu et al, 2005 ; Tofaris et al, 2006 ; Periquet et al, 2007 ). Also, the C-terminally truncated α-synuclein species assemble into filaments that resemble those found in diseased brains ( Crowther et al, 1998 ) and leads to the formation of pathological inclusions and neurotoxicity in transgenic mice ( Tofaris et al, 2006 ).…”
Section: Overview Of α-Synuclein Post-translational Modificationsmentioning
confidence: 99%
“…Concentrations spiked were 1 pM, 100 pM, 1 nM, 10 nM and 100 nM and samples were prepared in triplicate. The immunoprecipitation method for CSF samples was performed according to Bhattacharjee et al 2019 with minor modifications 64,65 . Briefly, after overnight incubation at 4 °C the KingFisher magnetic particle processor (Thermo where P is the probability that the observed match is a random event.…”
Section: Ap Of -Synuclein Spiked In Csf Followed By On-bead Digestionmentioning
confidence: 99%